الرقابة على العملية الانتخابية في ظل القانون العضوي 19.08مشرف محمد الطاهرجرمون الطالبين - عباسي, محمد العيد; فرحات, محمد طه (University of Eloued جامعة الوادي, 2020)
This study represented the issue of elections auditing process under the amendments mentioned in the Constitutional Law 08/19 amending and supplementing to the latter 10/16 related to the electoral system, so as to highlight the auditing mechanisms granted by the Algerian legislation through the different stages of the electoral process, and to focus on the qualitative guarantees that it has tasked recently, which had never been witnessed by the election system in Algeria, through its neutralization of the administrative apparatus - the Ministry of Interior - in managing, organizing and preparing the elections, and the creation of an independent national election authority granted it an administrative and financial independence from other authorities, and tasked it with managing and organizing the elections as well as supervising and auditing them. In this study we also mentioned the two most important types of auditing over the electoral process, namely administrative and judicial auditing, in all stages of the electoral process, so that we glanced the organizing processes for the elections, starting by calling the electorate and preparing electoral lists to running for candidacy and then the election campaigns. In the first chapter, we talked about about the voting phase. Then what derives from the subsequent stages of vote counting, focusing the results and announcing them, thus the appeals related to them in the second chapter.تتناول هذه الد ا رسة موضوع الرقابة على العملیة الانتخابیة في ظل التعدیلات التي أتى 10 المتعلق بنظام / 08 المعدل والمتمم للقانون العضوي 16 / بها القانون العضوي 19 الانتخابات ، وذلك لإب ا رز الآلیات الرقابیة التي كفلها المشرع الج ا زئري عبر مختلف م ا رحل العملیة الانتخابیة ، والتركیز على الضمانات النوعیة التي استحدثها مؤخ ا ر والتي لم یسبق وأن شهدها نظام الانتخابات في الج ا زئر من خلال تحییده للجهاز الإداري–و ا زرة الداخلیة- من إدارة وتنظیم وتحضیر الانتخابات ، واستحداث سلطة وطنیة مستقلة للانتخابات منحها استقلال إداري ومالي عن باقي السلطات الثلاث ، وكلفها بإدارة وتنظیم الانتخابات وكذا الإش ا رف والرقابة علیها . وقد تطرقنا في هذه الد ا رسة إلى أهم نوعین من الرقابة على العملیة الانتخابیة وهما الرقابة الإداریة والقضائیة ، وذلك في كل م ا رحل العملیة الانتخابیة ، بحیث تناولنا العملیات التحضیریة للانتخابات بدءا بمرسوم دعوة الهیئة الناخبة وإعداد القوائم الانتخابیة إلى الترشح ثم الحملة الانتخابیة في فصل أول ، تناولنا مرحلة التصویت وما یلیها من م ا رحل لاحقة من فرز للأصوات وتركیز للنتائج والإعلان علیها ، وكذا الطعون المتعلقة بها في فصل ثاني .This study represented the issue of elections auditing process under the amendments mentioned in the Constitutional Law 08/19 amending and supplementing to the latter 10/16 related to the electoral system, so as to highlight the auditing mechanisms granted by the Algerian legislation through the different stages of the electoral process, and to focus on the qualitative guarantees that it has tasked recently, which had never been witnessed by the election system in Algeria, through its neutralization of the administrative apparatus - the Ministry of Interior - in managing, organizing and preparing the elections, and the creation of an independent national election authority granted it an administrative and financial independence from other authorities, and tasked it with managing and organizing the elections as well as supervising and auditing them. In this study we also mentioned the two most important types of auditing over the electoral process, namely administrative and judicial auditing, in all stages of the electoral process, so that we glanced the organizing processes for the elections, starting by calling the electorate and preparing electoral lists to running for candidacy and then the election campaigns. In the first chapter, we talked about about the voting phase. Then what derives from the subsequent stages of vote counting, focusing the results and announcing them, thus the appeals related to them in the second chapter.
مذكرة ماستر
Keywords: the electoral process, voting, monitoring mechanisms, candidacy guarantees, independent authority, electoral commissions; العملیة الانتخابیة – الاقت ا رع – الآلیات الرقابیة – ضمانات الترشح – السلطة المستقلة – اللجان الانتخابیة .; the electoral process, voting, monitoring mechanisms, candidacy guarantees, independent authority, electoral commissions